ConstructÄ±ng a SustaÄ±nabÄ±lÄ±ty BusÄ±ness Model of a FertÄ±lÄ±zer Industry Based on Pentaple Bottom LÄ±ne: an ImagÄ±nary Research DÄ±alogue - Sukoharsono, Eko Ganis (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
Sustainability as a business model is a strategic tools to obtain company long term goals. This study is a postmodern imaginary research dialogue. The dialogue is between two people: Sustainable Accountant, and Senior Businessman. This research dialogue is based on the uses content analysis to analyze the practice of building strategic management sustainability through sustainability reports in a main fertilizer company in Indonesia. Next, the result of content analysis is compared to the Pentaple Bottom Line values: Planet, People, Profit, Phenotechnology and Prophet, in form of imaginary research dialogue too. This study found that the fertilizer company as the object of this study has implemented well the Pentaple Bottom Line values from the strategical step to the implementation step, and finally, it is reflected in the sustainability report.